2019
DOI: 10.1121/1.5093642
|View full text |Cite
|
Sign up to set email alerts
|

The percept of reverberation is not affected by visual room impression in virtual environments

Abstract: Humans possess mechanisms to suppress distracting early sound reflections, summarized as the precedence effect. Recent work shows that precedence is affected by visual stimulation. This paper investigates possible effects of visual stimulation on the perception of later reflections, i.e., reverberation. In a highly immersive audio-visual virtual reality environment, subjects were asked to quantify reverberation in conditions where simultaneously presented auditory and visual stimuli either match in room identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Previous studies showed that visual information of the room can improve auditory distance perception (Calcagno et al, 2012) and incongruent audio-visual cues can disrupt distance or externalization percepts (Gil-Carvajal et al, 2016). However, visual information has been shown to not affect the percept of reverberation (Schutte et al, 2019), which is in line with the results from the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that visual information of the room can improve auditory distance perception (Calcagno et al, 2012) and incongruent audio-visual cues can disrupt distance or externalization percepts (Gil-Carvajal et al, 2016). However, visual information has been shown to not affect the percept of reverberation (Schutte et al, 2019), which is in line with the results from the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Data relating to congruent versus incongruent audiovisual stimuli in an auditorium context is scarce, with one study finding that incongruent audiovisual stimuli from different seat locations sometimes but not always results in lower plausibility (Postma & Katz, 2017), one finding that congruent or incongruent audiovisual stimuli from different rooms did not significantly affect distance or room size perception (Maempel & Jentsch, 2013), while another has shown that perception of reverberation in a variety of rooms is not affected when the visual dimensions are altered to make the visual room incongruent with the auditory one (Schutte et al, 2019). In the study of Jeon et al (2008), when crossmatching 3 auditory and visual stimuli with different subjective preferences, a significant interaction was observed, although the effect size was very small compared to the main effects.…”
Section: Discussionmentioning
confidence: 99%
“…When the sound is far from listeners, reflected sound plays the main role in distance perception, while direct sound still obeys the inverse-square law. But Michael Schutte et al supposed that the estimation of subjects to reverberation did not depend on visual cues [ 26 ].…”
Section: Factors That Affect Sound Distance Perceptionmentioning
confidence: 99%